Characteristics of the intestinal tract microbiota in calves with various forms of acute catarrhal bronchopneumonia - N. Yu. Rodionova; E. V. Kulikov; E. D. Sotnikova; I. E. Prozorovskiy; Yu. A. Vatnikov; V. B. Rudenko; P. A. Rudenko (Ветеринария сегодня)
The intestinal barrier is one of the most important components that maintain gastrointestinal homeostasis, therefore changes in bacterial composition can lead to increased intestinal permeability and the development of intestinal translocation of opportunistic microorganisms, with the subsequent development or complication of various infectious diseases. A comparative description of the microbiota of the intestinal tract of calves with compensated, subcompensated and decompensated acute catarrhal bronchopneumonia of calves was carried out in the conditions of livestock farms of Vladimir and Moscow Oblasts. Calves aged 1–3 months with acute catarrhal bronchopneumonia (n = 37) were used for the study. The severity of the disease was assessed based on clinical and laboratory tests. The samples taken from clinically healthy animals (n = 8) were used as controls. It has been shown that in calves with compensated acute catarrhal bronchopneumonia, the qualitative and quantitative composition of the intestinal microbiome does not differ from clinically healthy animals. During the clinical manifestation of subcompensated and decompensated acute catarrhal bronchopneumonia in calves, a significant quantitative and qualitative shift in the microbiome occurs in the intestines, which indicates the occurrence of dysbiosis. We believe that this area is quite relevant and requires further scrupulous research.